2015
DOI: 10.3389/fphys.2015.00008
|View full text |Cite
|
Sign up to set email alerts
|

Differential signaling during macropinocytosis in response to M-CSF and PMA in macrophages

Abstract: The cellular movements that construct a macropinosome have a corresponding sequence of chemical transitions in the cup-shaped region of plasma membrane that becomes the macropinosome. To determine the relative positions of type I phosphatidylinositol 3-kinase (PI3K) and phospholipase C (PLC) in this pathway, we analyzed macropinocytosis in macrophages stimulated by the growth factor macrophage-colony-stimulating factor (M-CSF) and by the diacylglycerol (DAG) analog phorbol 12-myristate 13-acetate (PMA). In cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 45 publications
2
81
1
Order By: Relevance
“…However, the authors also found that the subsequent deactivation of Rac1 is equally important as it allows ruffle collapse and closure, which are essential for successful fluid capture. This is supported by quantitative microscopy studies that demonstrate that Rac1 is physiologically deactivated just prior to closure .…”
Section: Temporal Signals During Cup Formationmentioning
confidence: 69%
“…However, the authors also found that the subsequent deactivation of Rac1 is equally important as it allows ruffle collapse and closure, which are essential for successful fluid capture. This is supported by quantitative microscopy studies that demonstrate that Rac1 is physiologically deactivated just prior to closure .…”
Section: Temporal Signals During Cup Formationmentioning
confidence: 69%
“…However, M‐CSF induced macropinocytosis in macrophages are not inhibited by MK‐2206, one of Akt inhibitor. PI3K triggered PLCγ activates DAG, PKC, Ras, and finally closes the macropinosome . Other studies suggest that PDK1 activates PLCγ1 on residue Tyr783 in EGF induced MDA‐MB‐231 cells.…”
Section: Pdk1 Regulates the Phagocytosis Of Macrophagementioning
confidence: 94%
“…Phosphoinositide transitions initiated in ruffles carry through to the macropinosomes. The transition of PI(4,5)P2 to PI(3,4,5)P3 to PI(3,4)P2 and then to PI(3)P is conserved during the processes of macropinosome closure and maturation from C.elegans to mammalian cells 45 , 47 , 48 . PI3kinases are crucially involved in macropinocytosis and the broad spectrum PI3Kinase inhibitors, LY294002 and wortmannin blocks macropinosome formation, and specifically macropinosome closure, without necessarily affecting the preceding ruffling 42 , 49 , 50 .…”
Section: Macropinocytosismentioning
confidence: 99%
“…PI3kinases are crucially involved in macropinocytosis and the broad spectrum PI3Kinase inhibitors, LY294002 and wortmannin blocks macropinosome formation, and specifically macropinosome closure, without necessarily affecting the preceding ruffling 42 , 49 , 50 . The transient appearance of PI(3,4,5)P3 is accompanied by Rac1 activation and diacylglycerol production, and this is followed by the appearance of PI(3,4)P2 during macropinosome closure 48 . Lipid probes variably show accumulation of PI(3,4,5)P3 on the macropinosome membranes before or just after closure.…”
Section: Macropinocytosismentioning
confidence: 99%
See 1 more Smart Citation